Designer photonic dynamics by using non-uniform electron temperature distribution for on-demand all-optical switching times - Luke H. Nicholls (Nature Portfolio, 2019)
Here, the authors engineer a non-uniform electron temperature distribution through nanostructuring and demonstrate a sub-300 fs switching time. This can assist in the design of nanostructures for nonlinear optics, hot carrier extraction and photocatalysis